THE PERCEIVED ROLE OF GOD IN HEALTH AND ILLNESS: THE EXPERIENCE OF JAVANESE MOTHERS CARING FOR A CHILD WITH THALASSEMIA - Widayanti, Costrie Ganes (Faculty of Psychology, Diponegoro University, 2011)
Thalassemia is recognized as one of the major health problem in Indonesia. It is estimated that about 10% of Indonesian population are carrier of the mutated gene. Nevertheless Thalassemia is not well-understood by communities. This paper addresses how Javanese mothers view the role of God in Thalassemia. Semi-structured interview was employed to five mothers having a child with Thalassemia residing in Semarang, Central Java. Most mothers with Thalassemia children stated that Thalassemia was a result of bad consequence in the past, known as karma which they held at present. Having Thalassemia children would be perceived as ‘destiny’ and God’s trial to the family. All mothers agreed that acceptance (nrimo ing pandum) of the child’s condition without questioning to God was essential as a way to cope with. This result points to the cultural awareness that exits in community, to the need for health care providers to be sensitive to the health-related religious beliefs of patients and their families.Key words: Javanese mothers, Thalassemia, beliefs, nrimo ing pandum